NLO and NBO Analysis of Sarcosine-Maleic Acid by Using HF and B3LYP Calculations - N. Günay; H. Pir; D. Avcı; Y. Atalay (Journal of Chemistry)
We report a theoretical study on molecular structure, vibrational spectra, nonlinear optical (NLO), and natural bond orbital (NBO) analysis of sarcosine-maleic acid (C7H11NO6) in the ground state calculated by using the Hartree-Fock (HF) and density functional method (DFT/B3LYP) with 6–31++G(d,p) basis set. We repeat NBO calculations with 6–31G(d,p) basis set so as to see the diffuse function impact on NBO analysis. Stability of the molecule arising from hyper conjugative interactions and charge delocalization has been analyzed using NBO analysis. NBO analysis shows that there is a O–H⋯O and N–H⋯O hydrogen bond in the title compound, which is consistent with the conclusion obtained by the analysis of molecular structure. The calculated HOMO and LUMO energies show that charge transfer occurs within the molecule. Also, these results are supported by the NLO parameters. Finally, the calculated results were applied to simulate infrared and Raman spectra of the title compound which showed good agreement with experimental ones.